EFFECT OF FINANCIAL PERFORMANCE, AUDITOR REPUTATION, FIRM SIZE ON FIRM VALUE WITH MANAGERIAL OWNERSHIP AS MODERATING: (Empirical Study on Raw Goods Sector Companies listed on the Indonesia Stock Exchange for the period 2017-2020) - Rifki Adia Wardhana; Susi Sih Kusumawardhany (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to analyze the effect of financial performance, auditor reputation, and firm size on firm value with managerial ownership as moderating. This research is associative and descriptive with a quantitative approach, which uses secondary data. The population in this study are raw goods sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The sampling technique used purposive sampling so that the selected sample obtained as many as 17 companies. The analysis technique in this study uses panel data regression analysis using E-views version 10 software. The results of this study indicate that financial performance, auditor reputation, firm size simultaneously have a significant effect on firm value, financial performance has no significant effect on firm value, auditor reputation has no significant effect on firm value, firm size has a significant effect on firm value, managerial ownership cannot moderate the effect of financial performance on firm value, managerial ownership cannot moderate the effect of auditor reputation on firm value, managerial ownership can moderate the effect firm size on firm value, managerial ownership can moderate the effect of financial performance, auditor reputation, firm size on firm value simultaneously.